For want of wings a bird with teeth and a dinosaur in the family - Hunting, Jill 1950- (University of Oklahoma Press, 2022)
"Part detective history, part memoir, in this book Jill Hunting tells the story of her journey across the United States and into the realms of prehistory, national history, and family history as she follows her great-grandfather's trail to the fossil bed where he discovered an 83-million-year-old avian dinosaur"--